Developments on solar operated water desalination - Ahmed, Mirghani Ishak; Abakrb, Yousif A.; Ismail, Ahmad Faris (IIUM Press, 2011)
Various designs of solar stills ranging from minimal to technically advanced have been overviewed. Solar thermal systems that produce potable water from salty water have been studied for the last five years. The limitations of some types of solar stills have been pointed out. The multistage evacuated solar still was found to be of better output rate than the normal multistage systems. There is a great need to improve the design in order to utilise the multistage evacuated solar still concept.